Optimization of saponin extracts using microwave-assisted extraction as a sustainable biopesticide to reduce Pomacea canaliculata population in paddy cultivation - Ramli, N.H. (2019)
This study highlights the optimum conditions to extract saponins from Furcraea selloa var. marginata (Furcraea leaves) and spent tea leaves (STL) using supercritical-CO 2 (ScCO 2 ) and microwave. The bioactivity effects of saponins towards golden apple snails, Pomacea canaliculata were shown. The experiment was designed using the response surface methodology (RSM) to determine the optimum conditions for both extractions technique. Based on RSM analysis, the highest yield of saponins was obtained at 21.60 MPa, 0.30 mm particle size and 4.62 ml/min CO 2 for 30 min using ScCO 2 extraction. Meanwhile, in microwave-assisted extraction (MAE), the highest yield obtained was at 90 Â°C, 9 min of extraction time and 23.54 ml solvent per gram of sample. The effect of solvent was also investigated. Using water as co-solvent in ScCO 2 extraction and as solvent in MAE resulted in better yield of saponins. Overall, MAE was more efficient to extract saponins with 3.43 wt compared to ScCO 2 extraction with only 0.49 wt. The efficacy test of synthesized biopesticides against golden apple snails (GAS) proved that Furcraea leaves extract is the active ingredient to produce effective biopesticide as its performance was able to increase the mortality of GAS up to 100 within 24 h observation and enhanced the paddy growth at early stage of cultivation. Â© 2018 Elsevier B.V.